Average resonance parameters of Ti and Fe nuclei - M. M. Pravdivy; I. O. Korzh; M. T. Sklyar (Ядерна фізика та енергетика)
Full sets of the average resonance parameters S0, S1, '0R , '1R , S1,3/2 for Ti and Fe nuclei with natural mixture of isotopes are determined by means of the method designed by authors. The determination is realized from analysis of the average experimental differential cross sections of neutron elastic scattering in the field of energy before 440keV. Analysis of recommended parameters and of some of the literary data had been also performed.